Ferritin polarization and iron transport across monolayer epithelial barriers in mammals - Meyron-Holtz, Esther G.; Cohen, Lyora A.; Fahoum, Lulu; Haimovich, Yael; Lifshitz, Lena; Magid-Gold, Inbar; Stuemler, Tanja; Truman-Rosentsvit, Marianna (Frontiers in Pharmacology, 2014)
Epithelial barriers are found in many tissues such as the intestine, kidney and brain where they separate the external environment from the body or a specific compartment from its periphery. Due to the tight junctions that connect epithelial barrier-cells (EBCs), the transport of compounds takes place nearly exclusively across the apical or basolateral membrane, the cell-body and the opposite membrane of the polarized EBC, and is regulated on numerous levels including barrier-specific adapted trafficking-machineries. Iron is an essential element but toxic at excess. Therefore, all iron-requiring organisms tightly regulate iron concentrations on systemic and cellular levels. In contrast to most cell types that control just their own iron homeostasis, EBCs also regulate homeostasis of the compartment they enclose or the body as a whole. Iron is transported across EBCs by specialized transporters such as the transferrin receptor and ferroportin. Recently, the iron storage protein ferritin was also attributed a role in the regulation of systemic iron homeostasis and we gathered evidence from the literature and original data that ferritin is polarized in EBC, suggesting also a role for ferritin in iron trafficking across EBCs.